Effect of phenolic compounds Extraction of Green tea (Camellia sinsis. L) On the Glutathione of Alloxan Experimental InducedDiabeticRabbit. - Riffat Sarhat, Entedhar (Tikrit Journal of Pharmaceutical Sciences, 2023)
Diabetes Mellitus is considered as a member of oxidative stress syndrome. It is associated with an imbalance between types of free radicals and scavenger's system. This study showed the effect of the polyphenol compounds extracted from green tea (Camellia Sinesis L) on alloxan induced diabetic rabbits to determine their role in treatment of diabetes mellitus, their effect on enzymatic antioxidant and to know the histological effects on the diabetic kidney. The rabbits group was divided into five groups, cach group consist of 10 rabbits. The blood and tissue samples from these groups were taken for analysis and the result were as follow: There was a significant increase in Glucose .when polyphenol extract of green tea was used gave a significant decrease in all parameters (p<0.05) with dose rate of 100mg/kg of body weigt,200mgrkg of body weight as compared with diabetic group. There was a significant decrease in glutathione. When polyphenol extract of green tea was used with dose rate 100mg /kg of body weight gave a significant increase (p<0.05) in all parameters as compared with diabetic group.In comparison between the efficacy of herbs polyphenol compound in green tea. glibeneclamide it was appeared that the herbs are the better based on ¢ cy on treatment of diabetes and their effect on glucose and glutathione. The present results revealed that alloxan was effectively induced diabetes by partial destruction of b-cells of pancreas which lead to elevation of bload glucose level. As a consequence of hyperglycemia the abnormal effect was obvious in certain tissues in the body which attributed to the effect of diabetes Histological investigations shows that all the lesions in the kidney that result from diabetes such as hypertrophy, degeneration and hylanosis of the glomeruli.